Fly ash and nano-graphene enhanced stabilization of engine oil-contaminated soils - Ozlu, Veysel; Elif Firat, Muge (De Gruyter Poland Sp Z O O, 2025)
Due to urbanization and population growth, the redevelopment of contaminated areas has become popular. Engine oil, used for lubricating various engines, absorbs additional components from wear. Although used oils can be recycled if collected properly, they are often dumped, leading to groundwater and soil contamination. When incorporated into natural soils, these materials deteriorate environmental quality and adversely impact the geotechnical performance of the soil. This study investigates the impact of waste engine oil (EO)-contaminated kaolin (0, 3, 5, and 9%) on its physical and engineering behavior and evaluates the effectiveness of stabilization using fly ash at 0, 10, 25, and 45%, as well as nano-graphene at 0.04, 0.08, and 0.12%. The influence of contamination duration on these properties was thoroughly examined, and the optimal proportions of mineral additives and nanoparticle materials were identified through Gray Relational Analysis, ensuring enhanced precision in performance optimization. The results show that EO contamination increases the liquid limit due to the reduced water absorption capacity and increases the plastic limit to a greater extent, leading to a decrease in the plasticity index. The addition of fly ash (FA) and nano-graphene affects the physical properties differently based on the contamination levels. The water content of the contaminated kaolin decreased, while the dry unit weight increased. EO contamination reduces the unconfined compressive strength (UCS), and higher contamination degrees result in greater reduction. The inclusion of fly ash (FA) significantly enhances the UCS, with pronounced improvements observed at higher replacement ratios. The peak UCS enhancement occurred with the incorporation of 0.08% nanographene. However, both the degree of contamination and the addition of nanographene contributed to the increased brittleness of the soil matrix. The optimal gradation for maximum UCS was found to be 0.12% nanographene with 25% FA at 5% waste engine oil contamination. For the brittleness index, 10% FA and 0.04% nanographene are recommended for 3% engine oil contamination. The study concludes that the addition of mineral additives and nanoparticle materials can improve the geotechnical properties of contaminated soils, with fly ash and nano-graphene being effective additives.
Keywords: kaolin clay; waste engine oil contamination; nanoparticle; fly ash; soil stabilization